2018
DOI: 10.3892/mmr.2018.9589
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 is a key factor in the reversal effect of curcumin on multidrug resistance in the HCT‑8/5‑Fu human colorectal cancer cell line

Abstract: Multidrug resistance (MDR) is a major concern when using chemotherapy for the treatment of patients with colorectal cancer. MDR modulators are agents that can reverse MDR and, thus, enhance the chemosensitivity of tumor cells. The development of MDR modulators can improve the therapeutic efficacies of MDR in cancer. However, few effective MDR modulators have been identified so far. Curcumin has been reported to be an effective compound in the reversal of MDR in colorectal cancer cells. However, the mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Chemotherapy is an important means of treating colorectal cancer, but many patients show MDR during the course of chemotherapy, which is the main reason for treatment failure [3,4]. Chemotherapy for colorectal cancer consists mostly of three drugs, 5-FU, oxaliplatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy is an important means of treating colorectal cancer, but many patients show MDR during the course of chemotherapy, which is the main reason for treatment failure [3,4]. Chemotherapy for colorectal cancer consists mostly of three drugs, 5-FU, oxaliplatin.…”
Section: Discussionmentioning
confidence: 99%
“…MDR (also known as multidrug hold) occurs when a tumour cell develops antitumour drug resistance, in which different chemical structures exert different actions. Different antitumour drugs also produce cross-resistance [3,4]. Abnormal expression of drug-resistance proteins such as permeability glycoprotein (P-gp), annexin A1 (ANXA1), and ATP-binding cassette superfamily G member 2 (ABCG2) have been found in colorectal tumour tissues of patients with primary MDR, resulting in different levels of drug resistance to chemotherapy drugs in tumour cells [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…IC 50 value determines the concentration of drug at which 50% of cells survive. Drug Resistance Index (DRI) of 5FU on HeLa-R cells was calculated using the formula: IC 50 of resistant cells/ IC 50 of sensitive cells (41).…”
Section: Detection Of Cytotoxic Effects Of Sr033 5fu and Ptx On Helamentioning
confidence: 99%
“…Zhang et al demonstrated that curcumin was involved in MDR in colorectal cancer cell lines through a direct link with Nrf2. In fact, this compound, in combination with 5-FU, was able to induce apoptosis and reduce Nrf2 and Bcl-2/Bax expression, leading to a reversal effect on MDR in colon cancer [152]. Recently, Zhang et al revealed, for the first time, the involvement of DUB3—an alternative Nrf2 deubiquitinating enzyme—in chemoresistance occurring in colorectal cancer.…”
Section: Role Of Nrf2 In Ibd-associated Colorectal Cancermentioning
confidence: 99%